INTERNALIZATION OF EXOGENOUS DNA INTO INTERIOR COMPARTMENTS OF MURINE BONE MARROW CELLS - E. V. Dolgova; V. P. Nicolin; N. A. Popova; A. S. Proskurina; K. E. Orishchenko; E. A. Alyamkina; Y. R. Efremov; E. R. Chernykh; A. A. Ostanin; E. M. Malkova; O. S. Taranov; V. A. Rogachev; et al. (Вавиловский журнал генетики и селекции)
Injections ofexogenous DNAin combination witha cytostatic agent cyclophosphamide (CP) cause illness anddeathofexperimental mice. This phenomenon is referredto this as delayeddeath. It has been foundthat upon intraperitoneal injections fragments ofexogenous DNAreachthe bone marrowniche andenter the nuclei ofbone marrowcells (BMCs). Also, fragments ofexogenous DNAare capturedfrom culture medium byBMCs generatedex vivo. Upon suchtreatment, the fragments are incorporatedinto cells in a non-degradedform. We estimate that under suchconditions upto 1800 kb ofexogenous DNAcan be present in BMCs as fragments. After ex vivo incubation withBMCs, fragments ofexogenous DNAinternalizedin cells ofbothintact andCP pre-treatedmice become circularized. It has been shown that fragments ofexogenous DNAcan form high-molecular weight structures in vivo. Moreover, fragments localizedin BMCnuclei are suggestedto integrate into chromosome(s) ofrecipient mouse genomes when treatedwithCP andexogenous DNA.